Aproximações iniciais entre a praxiologia motriz e os jogos condicionados no ensino dos jogos esportivos coletivos - Bitencourt, William Daniel (Educación Física y Ciencia.)
Collective sports games are modalities that have, in their internal logic, peculiarities which give them a dynamic character for these motor practices. In this sense, the approximation of theories that systematize the teaching-learning process is of utmost importance for these modalities. Thus, this study aimed to establish relationships between the main concepts of Motor Praxiology and the driving force of conditional games tied to their teaching-learning process. For this, we carried out a theoretical research, presenting conceptual definitions of Motor Praxiology and Conditional Games, as well as the possible approximations of these proposals in collective sports games. In this way, it was found that, from the results presented, the teaching-learning process can be guided in these areas of knowledge, since they present expressive and vast advances for the teacher's pedagogical practice, bringing forth new knowledge to the teaching of collective sports games.